Taxes and obligations in the Kokan Khanate (Czech Journal of Multidisciplinary Innovations, 2023)
In this article, as in the Khiva khanates of Bukhara, the special aspects of different Shari'i, traditional, official, and extraordinary taxes established in the Khanate of Kokand, some benefits given to taxable persons, and labor obligations imposed on the population are described. will be done.